Pengaruh Tingkat Kedisiplinan Terhadap Kinerja Pegawai Pada Kantor Badan Narkotika Nasional (BNN) Kabupaten Tanjung Jabung Timur - Hezza Juni Dirta; Rahmi Handayani (Universitas Batanghari, 2020)
The purpose of this study was to determine the effect of the level of discipline on employee performance at the National Narcotics Agency (NNA) office in Tanjung Jabung Timur district. The variables tested in this study were the level of discipline and employee performance. The sample of this study is the Office of the National Narcotics Agency (NNA) of Tanjung Jabung Timur Regency. The survey was conducted by all 37 NNA employees. Testing the hypothesis in this study using simple regression analysis. Hypothesis testing results indicate that the level of discipline affects employee performance.